(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
In the wake of the Covid-19 pandemic, the Mendale Village Council in Central Aceh Regency has faced a range of public service challenges, including the low uptake of technology by village officials. This study aims to develop and implement an e-government-based Integrated Village Information System (SIMADU) in Mendale Village, Central Aceh Regency, to improve the quality of village public services. The study employs a mixed-methods approach, with data collected through observation, interviews, and Focus Group Discussions (FGDs). Qualitative data from interviews and FGDs were analysed using NVivo software to identify the needs and issues regarding village services. The results indicate that the Mendale Village Government requires an integrated information system to address administrative services that remain manual, limited transparency of information, and suboptimal management of BUMDes and tourism potential. SIMADU was developed and implemented through the stages of system planning, training for village officials, demonstrations, and implementation. This research produced a concept for the SIMADU website that integrates administrative services, BUMDes management, tourism information, health services, and cultural information as a model for digital-based public services at the village level.